DIGITAL MARKETING COMMUNICATION INTERACTION OF PROPERTY AGENTS ON THE BRIGHTON REAL ESTATE INDONESIA APPLICATION (BRIGHTON APPS) - Sunni, Efrizar; Farni Syam Maela, Nur'annafi (Proceeding of International Conference on Multidisciplinary Research, 2024)
The digital era has brought significant changes to behavior and interactions in property marketing, where applications have become a key element in marketing strategies. This research aims to analyze the digital marketing communication interactions by property agents through the Brighton Real Estate Indonesia application (Brighton apps) and identify its supporting and inhibiting factors. The method used is qualitative descriptive with a multicase approach, examining more than one case to gain a comprehensive understanding. Data were collected through interviews, observations, and documentation, with key informants consisting of agents, property owners, and buyers, who have deep insights into the app’s strategy and operations, as well as how the app is integrated into daily business processes. Data validity was tested through source triangulation, which serves to verify the accuracy of information from various informants. The research results show that the communication process begins with the uploading of property information into the application, which is then processed to attract potential clients. Agents utilize the app's features to communicate efficiently, both synchronously and asynchronously, which increases flexibility and work efficiency. The inhibiting factors in using this application include the agents' lack of familiarity with the app and technical challenges such as data maintenance or system updates, which may affect the overall user experience. However, the app is supported by a user-friendly design and reliable technology, resulting in rare technical issues. This research has important implications for the property marketing industry, especially in promoting the adoption of digital technology and enriching the literature on digital interactions in technology-based marketing.